Association of Pre-treatment Serum Fibrinogen-Albumin Ratio Index (FARI) and Concurrent Chemoradiotherapy (CCRT) Therapeutic Response in Patients with Locally Advanced Cervical Cancer (LACC) - Gezta Nasafir Hermawan; Bismarck Joel Laihad; Joice Margretha Mathilda Sondakh (RSUP Dr. Kariadi, 2025)
BACKGROUND: Cervical cancer is currently the second most prevalent women malignancy cases in Indonesia. High prevalence of cases diagnosed as locally advanced cervical cancer / LACC (FIGO Stage IIB-IVA), where concurrent chemoradiotherapy (CCRT) is the main treatment modality. Several therapeutic efficacy predictors in other malignancy cases including the pre-treatment serum fibrinogen-albumin ratio index (FARI) have been associated with therapeutic response to CCRT. However, there were no recent studies in cervical cancer cases. AIMS: To determine the association of pre-treatment FARI and CCRT therapeutic response in patients with LACC. METHOD: This is a prospective cohort study in patients with LACC from January – May 2024 whose clinical stage was determined. The pre-treatment FARI was calculated in patients who had met both inclusion and exclusion criteria, and undergone the CCRT regimen. Patients who completed the regimen were evaluated for therapeutic response. Data processing was carried out using SPSS 25 for Windows software. RESULT: In this study, it was found that the complete response (CR) group with the best outcome had the smallest pre-treatment FARI (9.79 ± 1.71), on the other hand the progressive disease (PD) group had largest pre-treatment FARI (33.72 ± 12.78). In addition, all CCRT therapeutic response groups had significantly different FARI values ​​(P value < 0.05) and the FARI cut point value of 12.44 had a sensitivity of 100% and a specificity of 78.1% for predicting complete response (CR) to CCRT. CONCLUSION: Low pre-treatment FARI is significantly associated with the likelihood of patients having a complete response (CR), which is the best outcome to CCRT.